1998
DOI: 10.1021/ja974024q
|View full text |Cite
|
Sign up to set email alerts
|

Time-Resolved Spectroscopic Studies of B12Coenzymes:  The Identification of a Metastable Cob(III)alamin Photoproduct in the Photolysis of Methylcobalamin

Abstract: Ultrafast transient absorption spectroscopy has been used to investigate the primary photochemistry of methylcobalamin. Approximately 27% of the initially excited methylcobalamin undergoes a bond homolysis on a subpicosecond time scale. The remaining 73% forms a metastable photoproduct with a spectrum similar to that of cob(III)alamin compounds. The ultraviolet absorption spectrum of the metastable photoproduct exhibits a prominent γ-band at 340 nm, characteristic of a cob(III)alamin with a very weak axial lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
199
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(214 citation statements)
references
References 50 publications
15
199
0
Order By: Relevance
“…For example, it is stated 56 that the spectrum of Intermediate C appears to be similar to the S 1 state seen in the photolysis of free MeCbl 601,61 . The S 1 state in MeCbl photolysis has now been characterised as a d/p → p* metal-to-ligand charge-transfer state 61 (consistent with theoretical density functional theory calculations) 62 , but was originally considered as 'a cob(III)alamin with a very weak axial ligand' 60 . The corresponding theoretical calculations for AdoCbl have not been completed to date but steady progress is being made with such calculations.…”
Section: Photochemistry Of Carhmentioning
confidence: 81%
“…For example, it is stated 56 that the spectrum of Intermediate C appears to be similar to the S 1 state seen in the photolysis of free MeCbl 601,61 . The S 1 state in MeCbl photolysis has now been characterised as a d/p → p* metal-to-ligand charge-transfer state 61 (consistent with theoretical density functional theory calculations) 62 , but was originally considered as 'a cob(III)alamin with a very weak axial ligand' 60 . The corresponding theoretical calculations for AdoCbl have not been completed to date but steady progress is being made with such calculations.…”
Section: Photochemistry Of Carhmentioning
confidence: 81%
“…56,58,60,65 To The dynamics of the photoinduced homolysis of B 12 cofactors were investigated on a time scale ranging from femtoseconds to nanoseconds, allowing for the detailed mechanism of Co-C bond photolysis to be obtained. In the case of CNCbl, it was found that the metastable S 1 state has a ligand-to-metal charge transfer (LMCT)…”
Section: Discussionmentioning
confidence: 99%
“…However, the excitation at 520 nm was followed only by formation of a long-lived S 1 state. 56,58,65 In contrast, the photolysis of AdoCbl was found to be wavelength independent resulting in a creation of a geminate radical pair within 100-130 ps at room temperature. 57,59,62 The same studies for ethyland n-propylcobalamin indicated the formation of radical pair when samples were excited at both 400 and 520 nm but the rapid dissociation contribution was mainly observed following the higher energy excitation.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations